How to scale a startup? The Use Bike case and the expansion of rent a bike service in Brazilian hotels - Araujo, Gianfranco da Silva; Schwade Junior, Odilo; Alberton, Anete; Marinho, Sidnei Vieira (REGEPE Entrepreneurship and Small Business Journal, 2023)
The "Use Bike" case presents César and his partners' dilemma in finding a way to expand their business. Initially, they have two choices: the sales method through trade representatives or the expansion by franchises. Business experience reveals the various challenges, as well as the advantages associated with each option. The use of trade representatives implies the need for more significant investment for acquiring bicycles and business expansion, i.e., challenges in terms of cash flow. However, creating a model for franchising that allows the reproduction of the business's success requires overcoming challenges and complexities. The presentation of these experiences, with information about the implementation of the project and considerations collected directly from the company's executives, allows the students to be able to discuss the entrepreneurial journey, from the validation of the business models and the possibilities of scalability of a startup that is not exclusively digital.